Pengaruh Elemen Fraud Diamond Terhadap Korupsi pada Pemerintah Daerah di Indonesia - Annisa Nabila Putri; Rindu Rika Gamayuni (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine how the four elements of the Fraud Diamond theory—pressure, opportunity, rationalization, and capability—affect corruption in Indonesian local governments during the 2022–2023 fiscal years. Using multiple linear regression analysis and secondary data from official reports, this research analyzes 105 local governments. The results show that only the opportunity element significantly affects corruption. This implies that less transparent budget management may create greater chances for corrupt practices. The study highlights the importance of strengthening internal control and transparency to mitigate corruption.